MENJADI KATOLIK INDONESIA DI TENGAH MAYORITAS (Menurut Ignatius Suharyo) - Patrisius Epin Du; Antonius Denny Firmanto (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
For Indonesian Catholics who are a minority group the idea of "Being Indonesian Catholics" needs to be explored continuously. As a minority Church often faced with difficult situations and causing fear of the people to be actively involved in life together in society. Using a method of critical reading of the idea of "Becoming an Indonesian Catholic" according to Cardinal Ignatius Suharyo's view, this study find the following points: First, being an Indonesian Catholic mean that the Church is actively involved in reviving the foundation of the Indonesian state, Pancasila in life with the light of Christian faith. Second, Catholics are called not to be afraid to speak out the truth in society, because Catholics are called to be salt and light in the community wherever they are sent. Third, Catholics have always developed a proactive dialogue attitude amidst plurality.